2011
DOI: 10.3390/polym3031377
|View full text |Cite
|
Sign up to set email alerts
|

Poly Lactic-co-Glycolic Acid (PLGA) as Biodegradable Controlled Drug Delivery Carrier

Abstract: In past two decades poly lactic-co-glycolic acid (PLGA) has been among the most attractive polymeric candidates used to fabricate devices for drug delivery and tissue engineering applications. PLGA is biocompatible and biodegradable, exhibits a wide range of erosion times, has tunable mechanical properties and most importantly, is a FDA approved polymer. In particular, PLGA has been extensively studied for the development of devices for controlled delivery of small molecule drugs, proteins and other macromolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

50
2,677
4
39

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 3,617 publications
(2,770 citation statements)
references
References 98 publications
50
2,677
4
39
Order By: Relevance
“…These data correspond to other work that indicates that the nature of release profiles in the later time points is due to polymer degradation [27]. The polyesters with higher amounts of lactide exhibit slower degradation rates due to the more hydrophobic characteristic of the lactide monomer with the extra methyl group that hinders water access [28]. Liu and Venkatraman confirmed this by demonstrating that a 75 mol% lactide PLGA ISFI degrades slower than a 50 mol% lactide polymer, and had NMP release profiles that generally agreed with those found here [27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These data correspond to other work that indicates that the nature of release profiles in the later time points is due to polymer degradation [27]. The polyesters with higher amounts of lactide exhibit slower degradation rates due to the more hydrophobic characteristic of the lactide monomer with the extra methyl group that hinders water access [28]. Liu and Venkatraman confirmed this by demonstrating that a 75 mol% lactide PLGA ISFI degrades slower than a 50 mol% lactide polymer, and had NMP release profiles that generally agreed with those found here [27].…”
Section: Discussionsupporting
confidence: 90%
“…The higher burst rate of polymers with higher lactide content, which agrees with literature [27], can also be attributed to hydrophobicity. Since lactide is more hydrophobic than glycolide [28], the higher amount of lactide will lead to polymers of lower hydrophilicity and a faster transition rate.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the lactic:glycolic acid ratio, the Mn of the PLGA backbone structure is important. From literature it can be concluded that with higher molecular weight slower degradation of the polymer is expected, and therefore a slower release of drugs can be hypothesized (Makadia and Siegel, 2011). This lower degradation and as a consequence slower release, is also however not visible in the first 10 to 20 days.…”
Section: Ova Release From the Particlesmentioning
confidence: 99%
“…Generally, NPs made of PLGA show a biphasic release profile, with an initial burst release followed by a sustained release phase (Makadia and Siegel, 2011). The fast initial burst release is induced by the fast release of protein at or near to the surface of the NP, whereas the sustained release is caused by additional and slower release of protein from the NP polymer matrix through channels.…”
Section: Ova Release From the Particlesmentioning
confidence: 99%
See 1 more Smart Citation